The evolution of weak standards: the case of the Swedish rheumatology quality registry. Issue 4 (23rd November 2016) - Essén, Anna; Sauder, Michael
Abstract: Research in sociology suggests that the effects of standards are not nearly as straightforward or as homogenising as they first appear. The present study extends these insights by demonstrating how even standards designed simply to collect data can produce extensive and unanticipated effects in medical fields as their uses evolve across actors and contexts. We draw on an embedded case study exploring the multifaceted consequences of the use of a practice‐driven voluntary documentation standard: the Swedish rheumatology quality registry from 1995–2014. Data collection included document analysis; 100 interviews with specialists, patients and stakeholders in the field; fieldwork; and observations of physician‐patient encounters. Our findings show that the scope and influence of the registry increased over time, and that this standard and its evolution contributed to changes in rheumatologist clinical practice, research practice, and governmental practice. These findings suggest that even initially 'weak', voluntary forms of standardisation can generate far‐reaching and unpredictable consequences for the performance and delivery of care as well as for the development of a medical field. Future work about how standards can contribute both to uniformity and diversity is warranted.